Research on innovative models of industry-education integration to promote sustainable education in agricultural machinery majors - Hua Zhang; Libao Wu; Ji Wang (Sustainable Futures)
This study investigates sustainability challenges in agricultural machinery education through a 2021–2023 survey of 238 students from Chinese agricultural universities. Quantitative analysis identifies three critical issues: inadequate cultivation of craftsmanship spirit (mean=2.46), shallow university-industry collaboration (mean=2.39), and misalignment between training programs and societal needs (mean=2.54). To address these challenges, we propose an innovative industry-education integration model characterized by tripartite (government-university-enterprise) cooperation. This model establishes a ''triple-chain'' linkage mechanism (innovation-talent-industry chains), which includes: (1) joint laboratories (87% participation rate in experimental group), and (2) digital twin platforms for agricultural machinery training. Empirical results indicate substantial significant improvements in vocational certification pass rates (73% in the experimental group vs 35% in control group) and patent conversion rates (37%). A controlled longitudinal experiment across three regions further underscores the model's effectiveness in enhancing craftsmanship spirit (Cohen's d = 1.82) and aligning curricula with industry demands . The research contributes novel insights by integrating regional agricultural characteristics into education policy design, offering a replicable framework for sustainable talent cultivation in agricultural engineering.